PENEGAKAN TINDAK PIDANA KORUPSI DI INDONESIA DARI ASPEK HUKUM PIDANA DI BIDANG EKONOMI (Studi Kasus: Penyalahgunaan Dana Bantuan Sosial) - Achmad Khozin Baharudin; Salsabila; Feren Nabilla (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2022)
Corruption is still a tradition for government officials, even during the Covid-19 pandemic, there are gaps of opportunity that are visible to them. In 2020, the social assistance program for handling Covid-19 is valued at around Rp. 5.9 trillion with a fee per food package of Rp. 10,000. In December 2021, the Corruption Eradication Commission (KPK) named the former Minister as a suspect in the alleged bribery case for social assistance in handling the Covid-19 pandemic in the Jabodetabek area in 2020 through a hand arrest operation. In fact, corruption and bribery are two inseparable things, where if there is corruption there must be several people behind it who accept bribes to launch the corruption. The purpose of this study is to analyze the emergence of allegations of corruption that occurred at the stage of filing a proposal for social assistance funds (bansos), and to understand conceptually the supervision of financial assistance (bansos) in the perspective of economic criminal law. This study uses a normative juridical method with a statutory approach and a case approach. The results of the study indicate that corruption has characteristics where corruption requires special handling and control from law enforcement officials and the role of the government in strictly controlling economic practices so that the potential for corruption can be prevented. Corruption is an extraordinary crime so extraordinary measures are needed (extraordinary enforcement) and extraordinary measures (extraordinary measures).